Decomposition of complete graphs into connected bipartite unicyclic graphs with eight edges - John Fahnenstiel; Dalibor Froncek (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2019)
We prove that each of the 34 non-isomorphic connected unicyclic bipartite graphs with eight edges decomposes the complete graph Kn whenever the necesary conditions are satisfied.